Efektivitas Program Guru Penggerak Kementrian Pendidikan Kebudayaan Riset dan Teknologi di SMP Negeri 3 Tumpaan - Christian Paskah Umboh; Florence D. J. Lengkong; Novva N. Plangiten (JURNAL ADMINISTRASI PUBLIK, 2023)
ABSTRACT The purpose of this study was to find out how the effectiveness of the Kemendikbubristek driving teacher program at SMP N 3 Tumpaan. This research uses a descriptive method with a qualitative approach. The effectiveness of the program can be judged by productivity, efficiency, flexibility, excellence, development. Data collection was carried out through observation, interviews, and literature studies with Miles and Huberman's analysis model data analysis techniques. Based on the results of research starting from the productivity of the mobilizing teacher program, it has been seen with the results of the mobilizing teachers being able to encourage students to develop in their environment at school, furthermore, the efficiency in implementing the mobilizing teacher program has been successful by comparing the results provided by the student apra with the learning provided by the mobilizing teacher at the SMP N 3 Tumpaan school. The suggestions from this study are expected that the driving teacher program will remain consistent and continue to be developed in its implementation. Keywords : Effectiveness, Programs, Teacher Mobilizer